Frankincense - gum olibanum : botany, oleoresin, chemistry, extraction, utilization, propagation, biotechnology, and conservation /: botany, oleoresin, chemistry, extraction, utilization, propagation, biotechnology, and conservation. (2023) - Unknown
No abstract available